The EFL teachers' challenges in implementing cooperative learning in reading classes : - Châu, Miêu Thanh (Đại học Cần THơ, 2019)
Based on the analysis of the researcher’s English learning and teaching context and results of previous studies, the present study was designed to reach two research aims. The first aim was to figure out the teachers’ challenges in implementing cooperative learning in reading classes. The second one was to study EFL teachers’ strategic system of how to have an effective implementation of cooperative learning in reading classes.